Future flooding and coastal erosion risks - Thorne, C. R.; Evans, Edward (College teacher); Penning-Rowsell, Edmund C. 1946- (Thomas Telford, 2007)
Presenting a forward look at the way risks associated with flooding and coastal erosion are likely to increase during the 21st century, this title examines the integrated measures necessary to manage future increases in risk.